Evaluation of Standard Heterosis for Grain Yield and Yield-Related Traits in Maize (Zea mays L.) Hybrids in West Gojam, Ethiopia - Taye, Wasihun Ewenetu; Abebe, Tiegist Dejene; Tiruneh, Mulugata Atnaf (International Journal on Food, Agriculture and Natural Resources, 2025)
Maize (Zea mays L.) is one of the most important cereal crops worldwide, leading in total crop yield production. However, the national average grain yield of maize in Ethiopia remains low. Hybrid development is one of the most widely used breeding strategies to improve maize productivity. Selecting promising germplasm with strong heterosis is essential for developing high-yielding maize varieties. Hence, the objective of this study was to evaluate the standard heterosis of the crosses for yield and yield-related traits. A total of thirty crosses, along with a widely used standard hybrid, were evaluated using a randomized complete block design (RCBD) with two replications during the 2018 cropping season at Adet. Analysis of variance showed significant difference among hybrids for all the studied traits except number of kernel per row (NKR) and ear length (EL). Percentages of standard heterosis in each trait were observed from negative to positive values. High amount of standard heterosis in grain yield was recorded in L4 x T2 (40.32%), L4 x T1 (40.30%) and L11 x T2 (24.95%) over the standard check BH 540.  Based on standard heterosis L4 x T1, L4 xT2 and L11 x T2 are promising crosses for development of hybrid varieties after additional verification of the results.Key words: Inbred lines, Standard heterosis, Maize (Zea mays L.) and Tester